White Masks on Black Skin: A Critical Examination of Black Identity and Psychological Trauma in Toni Morrison’s The Bluest Eye (Jagannath University Journal of Arts, 2026)
This article examines Toni Morrison‘s The Bluest Eye through the lens of Frantz Fanon‘s Black Skin, White Masks, highlighting how the pursuit of white beauty standards erodes the selfhood of Black individuals. Fanon explores the pressures imposed by a racist society that compels Black individuals to conform to white norms of beauty, only to leave them trapped in a futile cycle of rejection and self doubt. To exist and belong in a world that privileges whiteness, Black people often sacrifice everything in their struggle for acceptance. Despite relentless efforts to attain societal acceptance, Black individuals face an unbridgeable gap between their identity and the unattainable white ideal. This struggle often results in profound psychological distress, as they confront the impossibility of escaping their Blackness. Fanon asserts that Black individuals cannot shed their racial identity, and this conflict between their intrinsic Black identity and the oppressive expectations of a white-dominated society frequently culminates in a devastating loss of self-identity. In The Bluest Eye, Pecola Breedlove becomes the tragic embodiment of this struggle. Convinced that blue eyes would make her beautiful and worthy of love, she yearns for whiteness as the only escape from her suffering. However, as Fanon argues, black individuals cannot get rid of their racial identity, no matter how much they internalise white ideals. This tension produces profound psychological trauma. The Black subject is forced to negotiate between an imposed ideal of whiteness and their own lived reality of Blackness, a contradiction that inevitably leads to a fractured sense of self.Jagannath University Journal of Arts, v-15, i-01, 2025: p-113-122